A FDTD analysis on magnetized plasma of Epstein distribution and reflection calculation (vol 180, pg 55, 2009) - Ramadan, Omar (Elsevier Science Bv, 2010)
Recently, the shift operator finite difference time domain (SO-FDTD) method has been introduced by Yang [Computer Physics Communications 180 (1) (2009) 55-60) for modeling dispersive electromagnetic applications. This letter discuss the equivalence of this scheme and the well-known bilinear frequency approximation technique used in the field of digital signal processing. Although the SO-FDTD scheme looks different at first glance, it has been observed that it is fully equivalent to the bilinear frequency approximation technique. Consequently, the SO-FDTD scheme is indeed a bilinear transform operation which is unfortunately not cited by the author. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Shift operator finite difference time domain; Bilinear frequency approximation; Digital signal processing; Dispersive media